Overview of the evolution of agricultural mechanization in Nepal: A focus on tractors and combine harvesters - Takeshima, Hiroyuki (International Food Policy Research Institute, 2017)
This study was conducted to understand the evolution of agricultural mechanization in Nepal, specifically its determinants on both the demand and supply sides, as well as impacts on agricultural production and associations with broader economic transformation processes, in order to draw lessons that can be conveyed to other less mechanized countries. Mechanization levels in Nepal, a largely agricultural country, were relatively low until a few decades ago. However, significant mechanization growth, including the adoption of tractors, has occurred since the 1990s, against a backdrop of rising rural wages, particularly for plowing, combined with growing emigration and growth in key staple crop yields and overall broad agricultural production growth, as well as improved market access and participation. This growth in mechanization has taken place despite the general absence of direct government support or promotion. The growth of tractor use in the plains of the Terai zone has transformed agricultural production rather than inducing labor movement out of agriculture, raising overall returns to scale in intensification and enabling the cultivation of greater areas by medium smallholders than by resource-poor smallholders. Tractors have also facilitated the intensification of crop production per unit of land among very small farmers, enabling mechanization growth despite the continued decline in farm size, although these farmers may not have benefited as much as medium smallholders. Potential future research areas with policy relevance include mitigating accessibility constraints to tractor custom hiring services, identifying appropriate regulatory policies for mechanization, and providing complementary support to some smallholders who may not fully benefit from tractor adoption alone.